Characterization of artisanal honey produced on the Northwest of Portugal by melissopalynological and physico-chemical data - Feás, Xesús (2011)
Honey has always been regarded as a food which is advantageous for one’s health and as a product which has healing qualities. For this reason, is necessary to protect consumers from the fraudulent mislabeling of inferior honeys. The purpose of this study was to investigate some properties of artisanal honey samples (n = 45) collected from the Northwest of Portugal by using different honey analysis tests such as moisture, ash, pH, free acidity, electrical conductivity, hydroxymethylfurfural (HMF), apparent sucrose, reducing sugars and diastase activity. 77.8% of the total exceeded the quality parameters and should be labeled as ‘‘virgin” (humidity 618% and HMF 6 25 mg/kg). The present study found a linear correlation (y = 0.551x 0.089; R = 0.995) between the electrical conductivity of honeys and their ash content. All of the samples showed an Erica sp. pollen percentageP15%, and 42% of the total were monofloral Erica sp. In respect to coliforms and Salmonella’s presence, all the honey’s samples shown to be negative. The existence of sulphite-reducing Clostridia was low, and well below the established limit by MERCOSUR. Yeasts, moulds and aerobic mesophiles were detected in low amounts.